PENGARUH IMBANGAN HIJAUAN BERBANDING KONSENTRAT TERHADAP KECERNAAN BAHAN KERING, KECERNAAN BAHAN ORGANIK DAN KECERNAAN PROTEIN PADA KAMBING PE JANTAN DI LINGKUNGAN PANAS - Rama Dony FPA; Farida Fathul; Erwanto . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
This research aims to find out the influence of equilibration forage comparing concentrates to drydigestibility, organic digestibility and protein digestibility on male PE goat in the heatenvironment. Goats that were used as the sample were 3 male PE goast with body weight range(20.5 to 26.7 kg). This research used draft Longitude Cage Latin (RBSL), consisted of threetreatments (three periods), R1: 85% forage: 15% concentrate, R2: 70% forage: concentrate 30%,and R3: 55% forage: concentrate 45% . The water during the research is given by ad libitum. Theresults showed that: the equilibration forage comparing concentrates was not significant (P> 0.05)on dry digestibility, organic digestibility and protein digestibility.